Worldwide trends and future projections of fungal skin disease burden: a comprehensive analysis from the Global Burden of Diseases study 2021 - Li, Deng; Fan, Siqi; Zhao, Haochen; Song, Jiayi; Guo, Linfen; Li, Wei; Xu, Xuewen; Li, Qingfeng (Frontiers in Public Health, 2025)
BackgroundFungal skin diseases represent pervasive global health concerns, predominantly arising from dermatophytes, yeasts, and molds.ObjectiveThis study aimed to estimate the disease burden associated with fungal skin diseases in 2021. Additionally, it sought to analyze trends from 1990 to 2021 and forecast future patterns.MethodsThis observational study first utilized data from the Global Burden of Disease (GBD) database covering the years 1990 to 2021. We specifically used data from GBD 2021 to evaluate the global incidence, prevalence, and disability-adjusted life years (DALYs), disaggregated by age, gender, socio-demographic index (SDI), and GBD regions. Linear regression models were then employed to identify temporal trends, estimating the annual percentage change. Cluster analysis examined disparities across 45 GBD regions. To forecast future disease burden, we applied the age-period-cohort model and the autoregressive integrated moving average model.ConclusionIn 2021, there were approximately 1.73 billion global cases of fungal skin diseases. Males had higher age-standardized rates for incidence, prevalence, and DALYs compared to females. Age-specific analyses showed that although younger groups experienced the highest incidence rates, ASRs increased with age, especially among older populations. Regionally, low and middle SDI areas faced the greatest burden, with Asia having the highest incidence and Oceania the lowest. Projections suggest significant increases in incidence, prevalence, and DALYs, notably in middle- and low-income regions. These results highlight meaningful spatiotemporal disparities in fungal skin diseases and emphasize the need for strategic allocation of resources to mitigate these challenges and reduce the growing burden across various global populations.